Jakarta’s 2020 New Year Flood Assessment with a Rainfall–Runoff–Inundation (RRI) Model - Yeremia Immanuel Sihombing; Akbar Rizaldi; Mohammad Farid; N. Fajar Januriyadi; Idham Riyando Moe (Environmental Sciences Proceedings, 2023)
Floods hit Jakarta and several areas in the Ciliwung–Cisadane Watershed. The rain that occurred on 31 December 2019 stopped briefly and continued until 1 January 2020. As a result, several areas were flooded for several days. It is said that the rain that occurred was the largest in history. At least, the rainfall station at Halim Perdanakusuma Airport recorded rainfall with an intensity of 377 mm/day. That prompts a question about how much discharge was generated by the rainfall. This study was conducted to assess the flood discharge and the inundated area caused by the rain on 2020 New Year’s Eve. The rainfall–runoff–inundation (RRI) model was utilized to simulate the flood discharge and inundation using the 1D–2D hydraulic–hydrology model. This model also calculated infiltration and subsurface flow with the Green–Ampt equation. In addition, the rainfall data used rain data recorded by the ground station, and the topography used SRTM data from the United States Geological Survey (USGS). Then, the flood discharge obtained from the model was compared with the flood return period. The return periods of the flood that were compared were at 2, 5, 10, 25, 50 and 100 years. The results showed that the flood that occurred on 1 January 2020 was larger than the flood with a return period of 100 years. This means that rainfall had the biggest effect on the flood, rather than other factors.